Notes on Race and Gender in the USA: Poverty and Intersectionality - Castanyer, Prisca (Papeles de Europa, 2019)
This is the first of a series of multidisciplinary notes with one goal in common: to draw a much needed “bigger picture” on some basic human rights in the USA. To achieve this, we will present data from different studies as well as from the USA census. In this first note, we will examine overall poverty, unemployment, and wealth distribution in the USA while analyzing the unremitting socio-economic differences amongst the American population due to race and gender. Unfortunately, it is impossible for us to explain in depth all the reasons behind both racism and sexism due to the fact that these are rather ingrained complex issues with a long stance in America, despite multiple efforts to the contrary. We will, however, explore here the eugenics movement, which was quite influential during a good part of the 20th century, informing policies that would affect both women and people of color for decades. Unfortunately, the basic core beliefs of this movement are still present in the American ethos today and, under this new administration, basic human rights are constantly under attack, aggravating the already existing levels of poverty and equality amongst women and people of color. Subsequent notes will focus on women’s rights.